Developing a model system to investigate the epigenetic mechanisms underlying pluripotency in human cells - Matsa, Elena (2010)
Pluripotent human embryonic stem cells (hESCs) are a valuable tool for clinical therapies, drug testing and investigation of developmental pathways. Recently, over-expression of four pluripotency-associated genes (OCT4, NANOG, SOX2, and LIN28) has proven sufficient to reprogram differentiated cells into pluripotent stem cells, potentially alleviating the need for human embryos to isolate hESCs and opening new avenues for the investigation of pluripotency.